2019
DOI: 10.2196/12590
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback-Assisted Resilience Training for Traumatic and Operational Stress: Preliminary Analysis of a Self-Delivered Digital Health Methodology

Abstract: BackgroundPsychological resilience is critical to minimize the health effects of traumatic events. Trauma may induce a chronic state of hyperarousal, resulting in problems such as anxiety, insomnia, or posttraumatic stress disorder. Mind-body practices, such as relaxation breathing and mindfulness meditation, help to reduce arousal and may reduce the likelihood of such psychological distress. To better understand resilience-building practices, we are conducting the Biofeedback-Assisted Resilience Training (BAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Resilience-strengthening interventions have been used in several occupational settings to relieve workers' stress response [22]. Further investigation into this topic is worthwhile because smartphone applications may be more feasible to implement than other interventions, which are restricted by time and place [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience-strengthening interventions have been used in several occupational settings to relieve workers' stress response [22]. Further investigation into this topic is worthwhile because smartphone applications may be more feasible to implement than other interventions, which are restricted by time and place [23].…”
Section: Discussionmentioning
confidence: 99%
“…BT incorporates aspects of real-time RSA-biofeedback and shorter meditation practices. The BT has been studied previously in traumatic patients with positive results [23].…”
Section: Biofeedback Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches (e.g., sensorimotor psychotherapy and relaxation training) use interoception techniques (i.e., the noting of sensations, discomforts, pain, tension, pleasurers, and cues) to increase positive feelings toward physical sensations and help with integrating sensations and body regulation (78). Interventions including yoga (79), mindfulness-based stress reduction (80), and biofeedback (81) have been shown to reduce threat-responsive autonomic reactivity and have benefits for mental health. Additional research should explore their use as a therapeutic method or as part of a multi-method intervention to assist with coping during large scale crises such as the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…HRV measurement is regularly used as a biofeedback tool in mobile health (mHealth) interventions that target acute stress relief [45][46][47] but may also be useful for interventions that aim to provide users with feedback on their resilience over a longer timeframe. A recent literature review confirmed that HRV has potential as a biomarker for resilience but suggested that more longitudinal studies are needed that use wearable sensors to observe HRV in a naturalistic context of real-life and associate it with resilience-related outcomes, as most of the evidence is based on cross-sectional population studies [27].…”
Section: Aims Of This Studymentioning
confidence: 99%